Opioid Use 12 Months Following Interdisciplinary Pain Rehabilitation with Weaning. Issue 12 (5th August 2013) - Huffman, Kelly L.; Sweis, Giries W.; Gase, Allison; Scheman, Judith; Covington, Edward C.
Abstract Objectives To examine the frequency of and factors predicting opioid resumption among patients with chronic non‐cancer pain (CNCP) and therapeutic opioid addiction (TOA) treated in an interdisciplinary chronic pain rehabilitation program (CPRP) incorporating opioid weaning. Design Longitudinal retrospective treatment outcome study. Only those with addiction were counseled to avoid opioids for non‐acute pain. Setting Large academic medical center. Participants One hundred twenty patients, 32.5% with TOA. Participants were predominately married (77.5%), females (66.7%). Mean age was 49.5 (±13.7). 29.2% had lifetime histories of non‐opioid substance use disorders. Methods TOA was diagnosed using consensus definitions developed by American Academy of Pain Medicine, American Pain Society and American Society of Addiction Medicine to supplement Diagnostic and Statistical Manual of Mental Disorders, 4th edition, text revision (DSM‐IV‐TR) criteria. Non‐opioid substance use disorders were diagnosed using DSM‐IV‐TR. Data, including pain severity, depression and anxiety, were collected at admission, discharge and 12 months. Opioid use during treatment was based on medical records and use at 12 months was based on self‐report. Results Only 22.5% reported resuming use at 12 months. Neither patients with TOA nor patients with non‐opioid substance use disorders were more likely to resume use than those without substance use disorders. Only posttreatment depression increased the probability of resumption. Conclusions CNCP and co‐occurring TOA can be successfully treated within a CPRP. Patients report low rates of resumption regardless of addiction status. This is in marked contrast to reported outcomes of non‐medically induced opioid addictions. Prolonged abstinence may depend upon the successful treatment of depression.